Physicochemical Properties Of Sorghum (Sorghum Bicolor L.) Tempeh At Different Fermentation Times And Yeast Concentrations - Khairiah Khairiah; Sakina Yeti Kiptiyah; Ismi Fathiya Khoirunnisa; Shefira Nurunazmi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to determine the effect of yeast concentration and fermentation duration on the physical characteristics (texture and colour) as well as the chemical properties (moisture content, protein content, fat content, and crude fibre content) of sorghum tempeh. Methodology: A factorial Completely Randomised Design (CRD) was employed, comprising Factor I: fermentation time of 42 hours (L1), 48 hours (L2), and 54 hours (L3); and Factor II: yeast concentrations of 1.5% (K1), 1.8% (K2), and 2.0% (K3), each with three replications. Data were analysed using Analysis of Variance (ANOVA) at a 5% significance level, followed by Duncan’s multiple range test for post hoc comparison. Results: In terms of physical texture parameters, hardness, springiness, and H value were not significantly affected (P > 0.05). However, significant differences (P < 0.05) were observed in colour values (L*, a*, b*, C), texture parameters (cohesiveness and chewiness), and chemical properties (moisture, protein, fat, and crude fibre contents), all influenced by both yeast concentration and fermentation duration. Findings: The optimal treatment was identified in sorghum tempeh fermented with 1.8% yeast for 48 hours, which enhanced cohesiveness, chewiness, fat content, moisture, protein levels, and crude fibre, while reducing the physical attributes of hardness, springiness, and H value. Novelty : This study reveals that both yeast concentration and fermentation time significantly influence the physical and chemical characteristics of sorghum tempeh. Originality: The research specifically investigates the impact of varying yeast concentrations and fermentation durations on the quality attributes of sorghum-based tempeh. Conclusion: The physical and chemical properties of sorghum tempeh are significantly affected by the concentration of yeast and the duration of fermentation. Article Type: Experimental Research Article.